Les savoirs productifs - Emilio Andrés Martínez López; María de Ibarrola (Revue d'anthropologie des connaissances)
Based on in-depth interviews of 17 informal micro entrepreneurs of the garment industry in urban marginal areas of two Mexican cities, this paper argues the following proposals: a) The informal microenterprises are structured in a specific configuration of elements of production and labour that set up a work and income option available to the poor population in Latin America; b) The entrepreneurs who lead them put into play different kinds of “knowledge” (formal and informal) not only of technical nature but also of management production and the management of social networks that make up the market in which they are involved; c) Every small informal micro entrepreneur uses this knowledge in diverse and unique arrays as his/her major and most available resource, this particular knowledge makes sense of their productive activities and is the base in which to build and sustain their own business systems.